Association between β+252 tumour necrosis factor polymorphism and asthma in western Saudi children - Jiffri, Essam H. (2010)
There is strong evidence that supports the role of tumour necrosis factors (TNF-alpha/beta) as common genetic factors, located on 6p21.1–6p21.3 loci, in the pathogenesis of asthma disease. In this study, we extended our research work on TNFA to include the genotyping of Saudi asthmatic children as regards to TNFB gene (namely as lymphotoxin-α, LTA). We examined 60 asthmatic Saudi children compared to 56 healthy non-asthmatics using the PCR-RFLP analyses to identify the polymorphism +252A>G in intron 1 in lymphotoxin-α gene. We identified 55% of the allele A of the LTA∗NcoI polymorphism in subjects with asthma disease, and 45% of the allele G. In this study, the frequency of the LTA∗NcoI-A/A genotype was 40% preferably to the LTA∗NcoI-G/A and LTA∗NcoI-G/G genotypes. In addition, the severe persistent asthmatic cases were associated with the LTA∗NcoI-AA genotype at a frequency of 80%, while the genotype LTA∗NcoI-GG are associated with the mildest form of the disease. Consequently, one could predict the severity of asthma and hence the polymorphism of the LTA∗NcoI. Herein, we stated that more than 93% of Saudi children under investigation lived in the randomized areas of western regions of Saudi Arabia. In conclusion, genotype frequencies for the LTA+252 polymorphisms were significantly different from the controls. These findings may have implications for future early intervention studies by helping to identify infants at increased risk for wheezing and childhood asthma.